(untitled) (Asian Journal of Medical and Biological Research, 2017)
Hearing loss is a common disorder and can be conductive, sensorineural or mixed types. It can be congenital or acquired. In pediatric population more than 50% of deafness is genetic in origin. The patients may present as Deaf, mute or hard of hearing. Literature review was carried out on the pathophysiology including genetics, clinical presentation, etiology, diagnosis and various management, using internet Google, search PubMed. Additional information was obtained by cross referencing, using text and journals in the medical libraries. Asian J. Med. Biol. Res. March 2017, 3(1): 10-19